2012
DOI: 10.1039/c2ob26019k
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective phosphorylation and thiophosphorylation of N-confused porphyrin: a route to hybrid carbaporphyrinoids

Abstract: N-confused porphyrin (NCP) undergoes controlled regioselective phosphorylations at the inner, outer or both carbon atoms of the inverted pyrrole ring. Reactivity centered at the internal carbon atom is enhanced in the Ag(III) NCP's whereas the preference for perimeter substitution is characteristic of free base NCP. The addition of S(8) resulted in the formation of thio-derivatives containing 21-diphenylthiophosphoryl or 21-phosphinodithioic substituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…3) [20]. Later, its analogous complexes, 1d-Ag III , bearing perfluorinated arene moieties [16] and 1f-Ag III with p-toluene rings [21] were reported (Fig. 3).…”
Section: N-confused Porphyrins (Ncps)mentioning
confidence: 96%
See 1 more Smart Citation
“…3) [20]. Later, its analogous complexes, 1d-Ag III , bearing perfluorinated arene moieties [16] and 1f-Ag III with p-toluene rings [21] were reported (Fig. 3).…”
Section: N-confused Porphyrins (Ncps)mentioning
confidence: 96%
“…Three years later, the same authors reported a study that showed that the phosphorylation reaction is effected in the same conditions for complex 1f-Ag III ( Fig. 3) and also the products of thiophosphorylation of the complex are accessible by parallel routes affording a family of rare NCP hybrid ligands [21].…”
mentioning
confidence: 95%
“…The inner carbon atom, particularly in the form of a carbon−metal bond in the NCP core, is susceptible to various reactions such as alkylation, fluoroalkylation, nitration, oxygenation, sulfurization, and phosphorization . The inner‐C modification can thus largely tune the metal‐coordination environment of NCP, and consequently, an improvement of the catalytic activity or the creation of new catalytic reaction can be realized.…”
Section: Figurementioning
confidence: 99%
“…Figure 1. Chemical structures of free-base and metal complexes of NCP: (a) Tautomeric forms of NCP, (b) redox conversion of metal NCP complexes, (c) transformation of Ru-NCP complexes, and (d) Ru-NCP complexes used in this work.oxygenation, [9] sulfurization, [10,11] and phosphorization. [10b,c] The inner-C modification can thus largely tune the metal-coordination environment of NCP, and consequently, an improvement of the catalytic activity or the creation of new catalytic reaction can be realized.…”
mentioning
confidence: 99%
See 1 more Smart Citation